Autoserum: An Optimal Supplement for Bone Marrow Mesenchymal Stem Cells of Liver-Injured Rats - Qinglin Zhang; Xun Sun; Jianxun Ding; Ping He; Yujia Liu; Hongjing Cheng; Changlin Zhou; Xiangwei Meng (Stem Cells International)
Mesenchymal stem cells (MSCs) are an attractive source for the clinical cell therapy of liver injury. Although the use of adult serum, platelet lysate, or cord blood serum solves some of the problems caused by fetal bovine serum (FBS), the allogeneic immune response, contamination, and donor-to-donor and donor-to-receptor differences still obstruct the application of MSCs. In this study, the influences of autoserum from liver-injured rats (LIRs) and allogeneic serum from healthy rats on the isolation and culture of bone marrow MSCs (BMSCs) were examined and compared to FBS. The results showed that BMSCs cultured with autoserum or allogeneic serum exhibited better MSC-specific morphology, lower rate of cell senescent, and higher proliferation kinetics than those with FBS. In addition, autoserum promoted the osteogenic differentiation potential of BMSCs as allogeneic serum did. Although there were no significant differences in proliferation activity, immunophenotypic characterization, and differentiation potential between BMSCs cultured with autoserum and those with allogeneic serum, the potential adverse immunological reactions in patients with allogeneic material transplantation must be considered. We therefore believe that the autoserum from liver-injured patients may be a better choice for MSC expansion to meet the needs of liver injury therapy.